Posisi dan Manfaat Psikologi Pendidikan - Evianti Kristiani Sipahutar; Jenner Hutabarat; Dearma Damanik; Helena Turnip (International Forum of Researchers and Lecturers, 2025)
Educational psychology is a branch of psychology that focuses on understanding the learning process and the factors that influence educational success. This article aims to describe the strategic position of educational psychology in the context of the development of science and the modern education system, as well as the benefits of its application for educators, students and the educational environment. This research uses a literature review method by analyzing various relevant theories and previous research. The results of the study show that educational psychology has an important position as a bridge between learning theory and educational practice. Educational psychology helps identify students' learning styles, design effective teaching methods, and understand students' psychological needs. Apart from that, the application of educational psychology can increase learning motivation, overcome student behavior problems, and create a conducive learning environment. Thus, educational psychology not only contributes to the optimization of the teaching and learning process, but also to the holistic development of students' potential.